2022
DOI: 10.1007/s11701-022-01463-0
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory colectomy: a pathway for advancing the enhanced recovery protocol

Abstract: Enhanced recovery after surgery (ERAS) protocols employ multiple factors to decrease surgical stress and improve recovery (Lyon et al., World J Gastroenterol 18(40):5661–5663, 2012). These protocols use multimodal approaches to improve outcomes, including length of stay and morbidities (Lyon et al., World J Gastroenterol 18(40):5661–5663, 2012; Carmichael et al., Dis Colon Rectum 60:761–784, 2017). The ERAS guidelines have evolved since development; however, the question is posed of how to improve next (Lyon e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…The incidence of bradycardia was comparable between the propofol and remimazolam groups, a result similar to earlier published findings. 24 , 32 One study had suggested that the administration of remimazolam and propofol had lowered autonomic nerve activity judging by hemodynamic measurements and heart rate variability before and after anesthesia. 33 In patients undergoing cervical conization, bradycardia is a common concern because of the vagal reflex.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of bradycardia was comparable between the propofol and remimazolam groups, a result similar to earlier published findings. 24 , 32 One study had suggested that the administration of remimazolam and propofol had lowered autonomic nerve activity judging by hemodynamic measurements and heart rate variability before and after anesthesia. 33 In patients undergoing cervical conization, bradycardia is a common concern because of the vagal reflex.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously published our clinical algorithm for the SDD pathway. 6,7 Briefly, patients must have adequate social support at home, reliable access to telecommunication, demonstrate a firm understanding of all preoperative counseling and education, and have no need for postoperative new-ostomy teaching. We utilized our SDD protocol, an extension of ERAS, as we have previously reported.…”
Section: Clinical Management and Surgical Techniquementioning
confidence: 99%
“…Along with a few other researchers, our group has previously published the results of our same day discharge (SDD) after minimally invasive colectomies. [4][5][6][7] Yet there is scant examination of postoperative opioid requirements in this specific population and how they affect outcomes such as readmissions. Older work in the past has identified early discharge as a significant risk factor for readmission.…”
mentioning
confidence: 99%
“…25,26,29,31 As for type of procedures, six of the studies included all types of colorectal surgery 22,27,28,30,32 and eight studies included colectomies only. [24][25][26]29,31,[33][34][35] Seven studies assessed safety, feasibility and postoperative morbidity outcomes of twenty-four hours discharge, with or without home surveillance. [25][26][27][30][31][32][33] Seven of the studies assessed preoperative variables to identify patients who would be suitable for 24 hours discharge.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…[25][26][27][30][31][32][33] Seven of the studies assessed preoperative variables to identify patients who would be suitable for 24 hours discharge. 22,24,28,29,31,34,35 In-and exclusion criteria from included prospective studies are shown in ►Supplementary Table S2.…”
Section: Baseline Characteristicsmentioning
confidence: 99%